2017
DOI: 10.11113/mjfas.v13n4-2.840
|View full text |Cite
|
Sign up to set email alerts
|

Brainwave biomarkers of brain activity, physiology and biomechanics in cycling performance

Abstract: Generally, in sports performance, the relationship between movement science and physiological function has been conducted integrating neuronal mechanism over the past decades. However, understanding those interaction between neural network and motor performance comprehensively in achieving optimal performance is still lacking, mainly in cycling. The purpose of this study was to discuss the issues in neuroscience related to brain activity, physiology and biomechanics in achieving optimal performance in cycling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…The significant increase of the α/β ratio with IZ (Figure 4) could be due to the growing demand for sensorimotor, cognitive, and motor activity in the cycling task (Maceri, Cherup, & Hanson, 2019). Indeed, the β and the α cortical activities are both associated with psychological activities during aerobic exercise (Cheron et al, 2016;di Fronso et al, 2018;Enders et al, 2016;Ludyga et al, 2016;Zainuddin, Omar, Zulkapri, Jamaludin, & Miswan, 2017). Our results are in line with Enders et al, 2016, who reported an increase in both α and β bandwidth during a time trial to exhaustion (TTE) at 85% MAP .…”
Section: Xxxxfigure6xxxxsupporting
confidence: 83%
“…The significant increase of the α/β ratio with IZ (Figure 4) could be due to the growing demand for sensorimotor, cognitive, and motor activity in the cycling task (Maceri, Cherup, & Hanson, 2019). Indeed, the β and the α cortical activities are both associated with psychological activities during aerobic exercise (Cheron et al, 2016;di Fronso et al, 2018;Enders et al, 2016;Ludyga et al, 2016;Zainuddin, Omar, Zulkapri, Jamaludin, & Miswan, 2017). Our results are in line with Enders et al, 2016, who reported an increase in both α and β bandwidth during a time trial to exhaustion (TTE) at 85% MAP .…”
Section: Xxxxfigure6xxxxsupporting
confidence: 83%
“…Sports talent detection and development is currently actual and studied from various perspectives: genetic [1], relative age effect [2][3][4], brain activity [5][6], personal characteristics [7], social factors [8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, we aim to investigate the synchronous beta effects of listening to the acoustic stimulation from the Quranic Fatihah Chapter on human cognition and its neuroscientific explanation. EEG was used as a biomarker in various activities (Zainuddin et al, 2017), and this study was performed by conducting neuroimaging techniques using electroencephalogram (EEG) combined with multivariate analysis to see the potential of EEG as a biomarker for Quranic sound perception and its synchronous effects towards cognitive processes in the brain.…”
Section: Introductionmentioning
confidence: 99%